Cognitive and brain structural changes in long-term oligodendroglial tumor survivors. Issue 11 (9th August 2019) - Cayuela, Nuria; Jaramillo-Jiménez, Esteban; Càmara, Estela; Majós, Carles; Vidal, Noemi; Lucas, Anna; Gil-Gil, Miguel; Graus, Francesc; Bruna, Jordi; Simó, Marta
Abstract: Background: We identify cognitive impairment and MRI structural brain changes in long-term oligodendroglial tumor survivors treated with radiation therapy (RT) alone (21%) or with chemotherapy (CT) (79%). Methods: Oligodendroglial tumor patients (based on the World Health Organization [WHO] 2007 classification) who completed RT ± CT at least 2 years before the study initiation, were classified into 3 groups according to the time treatment was completed: Group 1 = 2–5 years ( n = 22), Group 2 = 6–10 years ( n = 13), and Group 3 >10 years ( n = 13). All patients had a cross-sectional neuropsychological evaluation ( n = 48) and a longitudinal volumetric analysis (gray matter [GM; n = 34]) between postsurgical and last follow-up MRI. White matter (WM) changes on MRI were assessed using a qualitative scale. Results: There were no differences regarding tumor or treatment-related characteristics between groups. Six of 22 patients (27.3%) in Group 1; 5/13 (38.5%) in Group 2; and 9/13 (69.2%) in Group 3 had cognitive impairment that was considered severe in 3/22 patients (13.6%) in Group 1; 4/13 (30.8%) in Group 2; and 6/13 (46.2%) in Group 3. Patients in Groups 2 and 3 showed significant GM atrophy and more leukoencephalopathy than Group 1. Cognitive deficits were associated with brain atrophy and WM changes. Conclusions: Long-term oligodendroglial tumor survivors who underwent standard RT ± CT treatment, mainly >5 years of its completion, present cognitive impairment, especially on memory and executive functions, associated with late GM and WM damage, thus highlighting the need of developing future strategies in patients with oligodendroglial tumor and long expected survival.